The world of Laura Ingalls Wilder : the frontier landscapes that inspired the Little House books - McDowell, Marta (Timber Press, 2017)
"This lushly illustrated book from bestselling author Marta McDowell examines Laura Ingalls Wilder's relationship to the landscape and illuminates how it inspired the beloved Little House Books" --